Insect physiological ecology mechanisms and patterns - Chown, Steven L.; Nicolson, Sue W. (Oxford biology, 2004)
"This book provides a modern, synthetic overview of interactions between insects and their environments from a physiological perspective that integrates information across a range of approaches and scales. It shows that evolved physiological responses at the individual level are translated into coherent physiological and ecological patterns at larger, even global scales.This is done by examining in detail the ways in which insects obtain resources from the environment, process these resources in various ways, and turn the results into energy which allows them to regulate their internal environment as well as cope with environmental extremes of temperature and water availability."--BOOK JACKET.